The Bears in the bed and the great big storm - Bright, Paul, 1949-; Chapman, Jane, 1970- (Intercourse, PA : Good Books, 2008)
One by one, three young bears crawl into Bear and Mrs. Bear's bed during a thunderstorm, certain they hear monsters outside, and although Bear tells each that monsters are not real, he later changes his mind.
2.4
K-3
Keywords: Bears -- Juvenile fiction; Bedtime -- Juvenile fiction; Fear -- Juvenile fiction; Thunderstorms -- Juvenile fiction; Bears -- Fiction; Bedtime -- Fiction; Fear -- Fiction; Thunderstorms -- Fiction; Bears -- Fiction; Bedtime -- Fiction; Fear -- Fiction; Thunderstorms -- Fiction